Child-Friendly Education Model for Violence Prevention in Islamic Boarding Schools - Sayyi, Ach.; Muslimin, Abdul Azis; Afandi; Fithriyah, Imaniyatul; Al-Manduriy, Shahibul Muttaqien; Ghaleb Alanesi, Abdul Salam Hamood (LETIGES, 2025)
This study originates from the rise in violence within faith-based educational institutions, especially Islamic boarding schools (Pesantren). This highlights the urgent need to develop educational approaches that prioritize child protection. Islamic Boarding School have significant cultural and spiritual authority, giving them the potential to pioneer child-friendly education principles. This research aims to formulate and examine a child-friendly Islamic education model for violence prevention at Islamic Boarding School. A qualitative case study approach was used. Data were collected through in-depth interviews, participatory observation, and document analysis. Analysis involved data description and categorization, thematic analysis and pattern recognition, theoretical interpretation, critical evaluation, model construction, validation, testing for credibility, and synthesis. Findings show the child-friendly Islamic Boarding School model is shaped by institutional policies like a “No Bullying” regulation. It also features ethical-spiritual values such as isthar (respect), tawadhu’ (humility), and pangabekti (devotion). Character habituation happens through riyadlah and mujahadah activities. Digital innovation, via the Ma’lūmat Santri application, strengthens participatory supervision that involves parents. This model reduces violence, reinforces character education, and enriches Islamic education theory based on humanistic values.